LEARNING OUTCOMES APPROACH IMPLEMENTATION: FUTURE PHYSICAL EDUCATION TEACHERS’ DIDACTIC COMPETENCE ASSESSMENT - Jansone, Rasma; Fernāte, Andra; Immere, Inta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Education process in Latvian Academy of Sport Education (LASE) is directed to provide all education level physical education (PE) teacher adequate preparation. Everyone in any country has the right to a quality education, which is determined by the contribution in student preparation, teacher qualification, learning environment organization, investment in education, and the planned outcomes. Contextual approach to quality is not determined; it depends on the creativity and continuous development. Learning outcomes assessment approach is the basis for an objective study achievement assessment. In the result of the research are obtained assessments of future PE teacher's ability to develop lessons, choose their content, conduct them using holistic approach, critically analyze their performance and make decisions for the improvement of their qualification. Education leaders will use the obtained results in long-term program changes.